Internet Of Things (Iot) In A Retail Environment. The New Strategy For Firmâ€™s Development - Nowodzinski, Pawel; Åukasik, Katarzyna; Puto, Agnieszka (European Scientific Journal, ESJ, 2016)
The mixture of the Internet and emerging technologies such as NFC (Nearfield Communications), real-time localization, and embedded sensors (beacons) transform ordinary objects (things) into smart objects that can recognize the state of the environment and react accordingly to the changing conditions or collect data. Internet of Things (IoT) is a new revolution of the Internet that is driven by the recent advancements in the world of: sensor networks, mobile devices, wireless communications and cloud technologies. Experts forecast that by the year 2020 there will be a total of 50 billion devices connected to the internet. The digitization of machines, cars, and other elements of the physical world is a influential idea. The IoT is starting to have a real impact by changing how goods are made and distributed, how products are serviced and refined. The article discusses the new business models and new strategy for the firms in order to achieve competitive advantage due to use the capabilities of the IoT, especially in the field of mobile sensors (e.g. iBeacons). Such a business model is probably the greatest opportunity in the next years to create growth in the digital economy.